Integrated Strategy in Designing an Effective Ship Ticket Sales and Scheduling Management System - Arifin, Nofri Yudi; Setyaudhi, Albertus Laurensius (YCMM, 2023)
In the era of globalization and technological advancements, shipping agencies play a central role in connecting regions, facilitating trade, and promoting the growth of the tourism industry. Ship ticket sales and travel scheduling are pivotal elements in the operations of a shipping agency. However, the challenges posed by operational complexity and intense competition necessitate innovative approaches to enhance efficiency and service quality. This research aims to design an integrated system that manages the processes of ship ticket sales and travel scheduling in XYZ Shipping Agency. In this approach, we identify key requirements through a preliminary study, design an effective system concept, and test the resulting model through simulations. The results of the research reveal that the integrated system holds the potential to enhance operational efficiency of the shipping agency, reduce potential errors, and provide superior services to customers. While real-world implementation challenges remain, the evaluation results provide a positive outlook on the potential of the integrated system in improving the agency's performance. This study contributes to the development of the integrated system concept for ship ticket sales and travel scheduling management in the shipping industry. However, further steps are required to test and implement this model in day-to-day operational settings, while adapting it to evolving technological advancements and shifting market demands.